Insights into Hydrocarbon Formation by Nitrogenase Cofactor Homologs - Lee, Chi Chung (mBio, 2015)
The L-cluster is an all-iron homolog of nitrogenase cofactors. Driven by europium(II) diethylenetriaminepentaacetate [Eu(II)-DTPA], the isolated L-cluster is capable of ATP-independent reduction of CO and CN(−) to C(1) to C(4) and C(1) to C(6) hydrocarbons, respectively. Compared to its cofactor homologs, the L-cluster generates considerably more CH(4) from the reduction of CO and CN(−), which could be explained by the presence of a “free” Fe atom that is “unmasked” by homocitrate as an additional site for methanation. Moreover, the elevated CH(4) formation is accompanied by a decrease in the amount of longer hydrocarbons and/or the lengths of the hydrocarbon products, illustrating a competition between CH(4) formation/release and C−C coupling/chain extension. These observations suggest the possibility of designing simpler synthetic clusters for hydrocarbon formation while establishing the L-cluster as a platform for mechanistic investigations of CO and CN(−) reduction without complications originating from the heterometal and homocitrate components.